The Long Methodist Union: A Case Study of Methodism in the Whitby Area of Yorkshire With a Focus on Methodist Union in 1932 and its Aftermath - Metcalfe, Christopher (The journal of religious history, literature and culture, 2023)
In 1932 the three Methodist denominations, the Wesleyan Methodists, the Primitive Methodists and the United Methodist Church were united to form a single Methodist Church. The impetus for union had come mainly from the leadership of the denominations who desired to create a more efficient and effective structure for evangelism in an increasingly secular society. However, it was left to the circuits and societies at the local level to determine how this vision was to be put into practice. This article discusses the local situational and the cultural factors that influenced the process of union in Whitby and, in particular, those that inhibited the desired outcomes of the leadership. The article argues that although the denominations legally became one Methodist Church in 1932, Methodist Union was a long process and there were many factors at the local level that determined the pace and the shape of union.